2001
DOI: 10.1046/j.0022-202x.2001.01515.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutation and Abnormal Expression of the p53 Gene in the Viral Skin Carcinogenesis of Epidermodysplasia Verruciformis

Abstract: Patients suffering from epidermodysplasia verruciformis are prone to nonmelanoma skin cancers, due to an inherited abnormal susceptibility to the oncogenic human papillomavirus type 5. Genotoxic sunlight ultraviolet B radiations are likely to be a cofactor. Lesions of two human-papillomavirus-type-5-infected epidermodysplasia verruciformis patients collected during an 8 y period were retrospectively studied for p53 mutations in exons 5 through 8 by a polymerase chain reaction single-strand conformation polymor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 46 publications
0
31
0
2
Order By: Relevance
“…Ultraviolet irradiation is supposed to play a synergistic co-carcinogenic role with HPV because in EV and in immunocompromised patients skin cancers occur predominantly on parts of the body exposed to UV radiation [58, 59]. The mechanism is not clear, but we can suppose that local photo-immunosuppression may increase the risk of HPV infection.…”
Section: Discussionmentioning
confidence: 98%
“…Ultraviolet irradiation is supposed to play a synergistic co-carcinogenic role with HPV because in EV and in immunocompromised patients skin cancers occur predominantly on parts of the body exposed to UV radiation [58, 59]. The mechanism is not clear, but we can suppose that local photo-immunosuppression may increase the risk of HPV infection.…”
Section: Discussionmentioning
confidence: 98%
“…This indicates that only a subset of EV HPV is endowed with an oncogenic potential. EV cancers usually arise on sun-exposed areas of the skin and a syncarcinogenic role of HPV5 and UVR is supported by the frequent mutations of the p53 gene in premalignant and malignant EV tumors (Padlewska et al, 2001).…”
mentioning
confidence: 99%
“…However, the malignant lesion of the patient in this report was located at the unexposed site (perianal region). Padlewska et al found the expression of oncoprotein p53 in the unexposed skin lesions of patients with EV and speculated that besides ultraviolet radiation, other unknown factors also play a key role in the development of EV malignant tumors [10]. This would be used to explain the occurrence of malignant transformation in the skin lesions of unexposed sites.…”
Section: Discussionmentioning
confidence: 99%